Evaluasi Penerapan Sistem Akuntansi terhadap Barang Milik Negara pada Sektor Publik (Studi Kasus pada Kepolisian Daerah Kalimantan Barat) - Muhsin, Muhsin; Rynandi, Oscar (Universitas Brawijaya, Indonesia, 2008)
This research has purposes to know and evaluate SABMN in assets management and Internal Control System to State's properties in public sector, especially job units in order to understand and to implement the Regulation No.1 year 2004 about State's Property Management, which states that in financial management in State Ministry or other governmental agencies, it is known the terms of budget usage and the authority of budger user on one hand and property usage and the authority of property user on the other hand. It also evaluates Financial Minister's decision No. 18/KMK.018/1999 to give property code number and location code to State's properties and justify the budget usage and State's properties user. Budget usage and the authority of budger user have to implement the Regulation of Financial Minister No.059/PMK.06/2005 about Accounting System and Financial report of central Government. The methodologies used in this research are literature and field study at District Police Department of West Kalimantan by using research instruments such as, interview guidelines, obervation guidelines, documentation, questionare. The data technique analysis is done through three processes: (1) Reducing data by summarizing or gathering potential data to answer the questions stated in the research. (2) Presenting data by organizing data in form of qualified information to enable the researcher to take a conclusion from the information obtained, (3) Concluding which means interpretating by finding something new. (Haberman & Miles, 1994:12). Based on the research result of SABMN at District Police Department of West Kalimantan. the writer can conclude that (1) Most of the price of State's properties which is stated in Property inventory Card (KIB) is based on the estimation so that the exact price of the properties is unknown. (2) The date when the properties received is also not stated properly, (3) In obtaining stock account value and other Stales properties accounts, the stock classification mapping to the stock estimatation in Standard Estimation Chart is not implemented because it is not applied yet in District Police Department of West Kalimantan, (4) Bensatker and all employees who are in charge of handling SABMN do not have deep understanding about it. (5) The output of SABMN is not complete yet because there are documents or reports which are not presented, like inventory stock book, because there is no program that can be used to input inventory stock so that inventory stock book is not made in SABMN.